2005
DOI: 10.1002/app.21364
|View full text |Cite
|
Sign up to set email alerts
|

Influence of zinc oxide during different stages of sulfur vulcanization. Elucidated by model compound studies

Abstract: The addition of zinc oxide (ZnO) as an activator for the sulfur vulcanization of rubbers enhances the vulcanization efficiency and vulcanizate properties and reduces the vulcanization time. The first part of this article deals with the reduction and optimization of the amount of ZnO. Two different rubbers, solution-styrene-butadiene rubber and ethylene-propylene-diene rubber, have been selected for this study. The results demonstrate that the curing and physical properties can be retained when the level of ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
104
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 23 publications
(24 reference statements)
2
104
0
4
Order By: Relevance
“…It has also attracted attention as a promising phosphor for field emission displays (FEDs) [2] compared with the conventional sulfide phosphors. The biggest users of ZnO are manufacturers of rubber; the content of ZnO in vulcanized rubber can be reduced to 10 times if nanosized ZnO is used instead of the conventional micro ZnO [3]. Previous research reports [4][5][6] revealed that the vulcanized rubber products can last longer and have improved properties if nanosized ZnO is used as the activator and accelerator instead of micro ZnO, and this approach in turn can greatly reduce the quantity of micro ZnO in the vulcanization of rubber [5,6] and the release of toxic zinc metal into the environment [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has also attracted attention as a promising phosphor for field emission displays (FEDs) [2] compared with the conventional sulfide phosphors. The biggest users of ZnO are manufacturers of rubber; the content of ZnO in vulcanized rubber can be reduced to 10 times if nanosized ZnO is used instead of the conventional micro ZnO [3]. Previous research reports [4][5][6] revealed that the vulcanized rubber products can last longer and have improved properties if nanosized ZnO is used as the activator and accelerator instead of micro ZnO, and this approach in turn can greatly reduce the quantity of micro ZnO in the vulcanization of rubber [5,6] and the release of toxic zinc metal into the environment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanism during vulcanization process [4,8,9,12] and its effects on the properties of the vulcanizates [3][4][5][6][7]9,11] has long been known and investigated. However, ZnO release into the environment that occurs during production, disposal and recycling of rubber products, which is in soluble zinc compounds is classified as ecotoxic to aquatic organisms [5,7,[9][10]. Moreover, usage of ZnO is also associated with a problem related to mold fouling that occurs during rubber manufacturing [9,[13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, ZnO release into the environment that occurs during production, disposal and recycling of rubber products, which is in soluble zinc compounds is classified as ecotoxic to aquatic organisms [5,7,[9][10]. Moreover, usage of ZnO is also associated with a problem related to mold fouling that occurs during rubber manufacturing [9,[13][14]. There is evidence that during vulcanization, a considerable amount of ZnO is consumed and transformed into zinc sulfide (ZnS), which is a by-product of the vulcanization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These authors also compared the effect of different metal oxides with EPDM 9 and SBR. 9,13 In EPDM with tetramethylthiuram disulphide (TMTD) as accelerator, none of the metal oxides studied was as active as ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…9,13 In EPDM with tetramethylthiuram disulphide (TMTD) as accelerator, none of the metal oxides studied was as active as ZnO. In SBR with TBBS as accelerator, the substitution of ZnO by MgO did not cause large effects on the cure and physical properties.…”
Section: Introductionmentioning
confidence: 99%